1999
DOI: 10.3141/1666-04
|View full text |Cite
|
Sign up to set email alerts
|

Automated Bus Dispatching, Operations Control, and Service Reliability: Baseline Analysis

Abstract: This paper presents findings on initial changes in service reliability following Tri-Met's deployment of a new bus dispatching system using automatic vehicle location and automatic passenger counter technology. Changes in on-time performance, headway variation, run time variation, and run times were determined with respect to pre-deployment levels. Changes in headway variation and run times were also used to estimate the initial benefits of the new system with respect to operating costs, passenger waiting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 8 publications
(14 reference statements)
5
73
0
Order By: Relevance
“…The archived AVL/APC data have been used in various studies of operations control and service reliability (Strathman et al 1999;Strathman et al 2000;Strathman et al 2001a;Strathman et al 2001b), for route-level passenger demand modeling (Kimpel 2001), for models of trip and dwell time (Bertini and El-Geneidy 2004), and for evaluating schedule efficiency and operator performance (Strathman, et al 2002).…”
Section: Computer-aided Dispatch (Cad) Centermentioning
confidence: 99%
“…The archived AVL/APC data have been used in various studies of operations control and service reliability (Strathman et al 1999;Strathman et al 2000;Strathman et al 2001a;Strathman et al 2001b), for route-level passenger demand modeling (Kimpel 2001), for models of trip and dwell time (Bertini and El-Geneidy 2004), and for evaluating schedule efficiency and operator performance (Strathman, et al 2002).…”
Section: Computer-aided Dispatch (Cad) Centermentioning
confidence: 99%
“…Using the travel-time estimation, average commercial speed of the buses was also estimated 8 . After the travel-time estimation and prediction studies, the travel-time variability (TTV) and reliability studies were reported 5,[9][10][11][12] . Day-to-day and period-toperiod travel-time reliability analysis was also carried out earlier 13 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are a number of studies that have analysed bus TTV based on empirical data (e.g., Abkowitz and Engelstein, 1983;Strathman and Hopper, 1993;Strathman et al, 1999;El-Geneidy et al, 2008;Mazloumi et al, 2010;Moghaddam et al, 2011). Common indicators proposed to assess the reliability of a public transport service include the standard deviation of travel time, the probability of on-time performance 2 , the travel time ratio (observed travel time/scheduled travel time), the average additional travel time per passenger (Van Oort, 2011) and measures to analyse the variability of headways.…”
Section: Determinants Of Travel Time Variability: the Case Of Public mentioning
confidence: 99%